2012
DOI: 10.1152/ajprenal.00191.2012
|View full text |Cite
|
Sign up to set email alerts
|

A regulated NH2-terminal Sgk1 variant with enhanced function is expressed in the collecting duct

Abstract: Raikwar NS, Liu KZ, Thomas CP. A regulated NH2-terminal Sgk1 variant with enhanced function is expressed in the collecting duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…We also reported that its encoded protein sgk1_i3 is more stable compared to sgk1 and that it stimulates apical epithelial Na + transport when expressed in FRT and in mpkCCD c14 cells (Raikwar et al. ). Sgk1 and Sgk1_i3 differ only in the NH 2 terminus where 25AA in Sgk1 is replaced by 39 AA in Sgk1_i3.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We also reported that its encoded protein sgk1_i3 is more stable compared to sgk1 and that it stimulates apical epithelial Na + transport when expressed in FRT and in mpkCCD c14 cells (Raikwar et al. ). Sgk1 and Sgk1_i3 differ only in the NH 2 terminus where 25AA in Sgk1 is replaced by 39 AA in Sgk1_i3.…”
Section: Resultsmentioning
confidence: 92%
“…We previously showed that Sgk1_v3 is an aldosterone‐regulated transcript and that Sgk1_i3, like Sgk1, stimulates ENaC mediated Na + transport (Raikwar et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SGK1 has also been shown to enhance cell-surface expression of SLC6A19 in Xenopus oocytes [25]. Since SGK1 has five isoforms (SGK1a-e) [28][29][30], a primer pair from the conserved region of these isoforms was chosen so that the total mRNA level was measured by qRT-PCR.…”
Section: Reduced Sgk1 Mrna Expression In Tis7mentioning
confidence: 99%